2021
DOI: 10.3389/fpsyg.2021.722261
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception Supports Adults in Numerosity Processing and Arithmetical Performance

Abstract: Previous studies have found a correlation between numerosity processing and arithmetical performance. Visual perception has already been indicated as the shared cognitive mechanism between these two; however, these studies mostly focused on children. It is not clear whether the association between numerosity processing and arithmetical performance still existed following the development of individual arithmetical performance. Consequently, the underlying role of visual perception in numerosity processing and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
(140 reference statements)
0
0
0
Order By: Relevance
“…Alternative models suggest dual separated symbolic/non-symbolic representations [ 12 , 13 ] or a progressive differentiation of magnitude representation systems with age [ 14 , 15 ]. Some evidence has also suggested that arithmetic skills rely on other cognitive mechanisms, such as working memory [ 16 – 18 ] or visuospatial perception [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative models suggest dual separated symbolic/non-symbolic representations [ 12 , 13 ] or a progressive differentiation of magnitude representation systems with age [ 14 , 15 ]. Some evidence has also suggested that arithmetic skills rely on other cognitive mechanisms, such as working memory [ 16 – 18 ] or visuospatial perception [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%